I recognise your name but I can't remember your face: An advantage for names in recognition memory. Issue 7 (July 2019) - Burton, A Mike; Jenkins, Rob; Robertson, David J
Forgetting someone's name is a common failure of memory, and often occurs despite being able to recognise that person's face. This gives rise to the widespread view that memory for names is generally worse than memory for faces. However, this everyday error confounds stimulus class (faces vs. names) with memory task: recognition versus recall. Here we compare memory for faces and names when both are tested in the same recognition memory framework. Contrary to the common view, we find a clear advantage for names over faces. Across three experiments, we show that recognition of previously unfamiliar names exceeds recognition of previously unfamiliar faces. This advantage persists, even when the same face pictures are repeated at learning and test—a picture-memory task known to produce high levels of performance. Differential performance between names and faces disappears in recognition memory for familiar people. The results are discussed with reference to representational complexity and everyday memory errors.